Analysis of a novel 3C-SiC thin layer on silicon diaphragms for enhanced stress amplification in MEMS piezoresistive pressure sensors - Nguyen Chi Cuong; Trinh Xuan Thang; Lam Minh Thinh; Vuong Dinh Duy Phuc; Truong Huu Ly; Ngo Vo Ke Thanh; Le Quoc Cuong (Vietnam Journal of Science, Technology and Engineering, 2024)
This study analyses the square diaphragm structure of a micro-electro-mechanical system (MEMS) pressure sensor using the finite element method (FEM). The research investigates an enhancement in stress distribution achieved by coating a silicon (Si) diaphragm with a thin layer of silicon carbide (3C-SiC). Applying a thin layer of 3C-SiC material onto a Si diaphragm enhances the stress distribution of MEMS pressure sensors. The design structure of the square diaphragm of a MEMS pressure sensor is simulated and analysed using 3D FEM in COMSOL multiphysics. Four piezo-resistors are configured in a Wheatstone bridge to translate resistance variations into an output voltage. Then, the stress distributions are calculated by solving the 3D structures of MEMS pressure sensors in the stationary solver of the solid mechanics module in COMSOL multiphysics. The findings indicate a significantly higher stress distribution in the 3C-SiC layer compared to a solely silicon diaphragm. Consequently, it is posited that the stress distribution in MEMS pressure sensors could be considerably augmented with increasing pressure, increasing diaphragm length, and decreasing diaphragm thickness. Also, the output voltage of more than 20 mV can be achievable with this design for using the thin layer of 3C-SiC material on a Si diaphragm in designing MEMS piezoresistive pressure sensors.